Provincial Historical Archives and Documentary Appraisal in Spain - Flores Varela, Carlos (Revista General de Información y Documentación, 2020)
The article analyzes the role of the Provincial Historical Archives (AHP) in the mechanisms of documentary appraisal in Spain, both in the General State Administration and in the Autonomous Communities. The presence of the AHPs in the evaluation committees, their weight in the set of assessed documentary series and, when possible, the consequences in terms of volume of eliminated documentation are studied.